Chinese quince seed gum and poly (N, N-diethylacryl amide-co-methacrylic acid) based pH-sensitive hydrogel for use in drug delivery. (1st April 2018) - Xie, Ai-Jun; Yin, Hui-Shuang; Liu, Hua-Min; Zhu, Chun-Yan; Yang, Ya-Jie
Highlights: A novel Chinese quince seed gum based hydrogel was synthesized. The chemical structures and pH-sensitive properties were examined. CQSG/poly (DEA-co-MAA) hydrogels have promising potential for oral delivery of drugs. Abstract: In this investigation, a variety of innovative pH-sensitive polymers consisting of Chinese quince seed gum (CQSG) and poly ( N, N -diethylacryl amide-co-methacrylic acid) were synthesized via free radical polymerization for controlled drug delivery. The resultant hydrogel polymers were characterized by scanning electron microscopy and X-ray diffraction, analyzed by Fourier-transform infrared spectroscopy, and confirmed with thermogravimetry. Results suggested the hydrogel polymers were composed of CQSG chains physically entangled in poly ( N, N -diethylacryl amide-co-methacrylic acid) networks. Swelling properties of these hydrogels were strongly affected by the contents of CQSG and crosslinkers. The drug delivery applications of the hydrogels were evaluated using bovine serum albumin (BSA) as a model drug in vitro release. It was determined that BSA release from the hydrogels was pH-sensitive under simulated gastrointestinal conditions. All of these attributes imply that the new proposed CQSG/poly ( N, N -diethylacryl amide-co-methacrylic acid) hydrogel polymers can be used as a good medium for oral delivery of proteinaceous drugs.